PROGNOSTIC ROLE OF A1166C POLYMORPHISMS OF THE ANGIOTENSINE II RECEPTOR GENE (AGT2R1) IN CORONARY ATHEROSCLEROSIS AMONG ADYGHEA REPUBLIC INHABITANTS - T. M. Ashkanova; D. V. Muzhenya; A. R. Pshidatok; A. R. Tuguz; I. V. Smolkov; D. S. Shumilov (Российский кардиологический журнал)
Aim. The investigation of A1166/166C polymorphisms of the vascular receptor 1 type of angiotensine II gene (AGT2R1) association with the development of coronary and peripheral atherosclerosis in ethnic groups ofAdygheaRepublicinhabitants.Material and methods. The spread of A1166/166C polymorphic variants of the gene AGT2R1 was studied via the “single nucleotide polymorphism” (SNP) — method with allele-specific primers and electrophoretic results detection (by SPF “Litech”). Gene polymorphisms AGT2R1 (rs5186) with nucleotide replacement of adenine by cytosine (А>C) in the 1166th position of gene AGT2R1 were typified in the samples of donors genomic DNA (n=143) and of those with cardiovascular diseases (n=39) at the age 23-65 y. o. from two ethnic subgroups — Adyghes and Russians. The data was processed via software SPSS Statistics 17.0.Results. In the group of those with complicated coronary and peripheral atherosclerosis there was statistically significant increase of the prevalence of mutant1166Callele and of pathological monozygous genotype C1166C. The risk of cardiovascular diseases in the carriers of1166Callele increases 3,77 times (c2 =26,07; р=0,00003), and in the case with homozygous “mutant” CC genotype — 10,36 times (c2 =31,20; р=0,00002), that makes it to use the1166Callele and С1166С genotype AGT2R1 as genetic predictors of coronary atherosclerosis and markers of prenosological diagnostics of ischemic heart disease (c2 =42,96; р=0,0000005; OR (95%)=17,37).Conclusion. The results of this study, together with additional instrumental investigations of cardiovascular system functioning will help to improve the precision of diagnostics of atherosclerosis and its possible complications at earlier stages, that will help to decrease disability rate and mortality in economically active citizens.